Răspuns :
[tex] \frac{14}{49} - \frac{5}{35} [/tex]
Se simplifică
[tex] \frac{14}{49} [/tex]
cu 7
[tex] \frac{14}{49} = \frac{2}{7} [/tex]
Se simplifică
[tex] \frac{5}{35} [/tex]
cu 5
[tex] \frac{5}{35} = \frac{1}{7} [/tex]
[tex] \frac{14}{49} - \frac{5}{35} = \\ \frac{2}{7} - \frac{1}{7} = \\ \frac{2 - 1}{7} = \\ \frac{1}{7} [/tex]
Se simplifică
[tex] \frac{14}{49} [/tex]
cu 7
[tex] \frac{14}{49} = \frac{2}{7} [/tex]
Se simplifică
[tex] \frac{5}{35} [/tex]
cu 5
[tex] \frac{5}{35} = \frac{1}{7} [/tex]
[tex] \frac{14}{49} - \frac{5}{35} = \\ \frac{2}{7} - \frac{1}{7} = \\ \frac{2 - 1}{7} = \\ \frac{1}{7} [/tex]